2021
DOI: 10.1155/2021/6689247
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Antinutritional Content, Microbial Load, and Sensory Acceptability of Noodles Formulated from Moringa (Moringa oleifera) Leaf Powder and Wheat Flour Blend

Abstract: Background. Noodle products are popular throughout the world, and they can be prepared from cereal like wheat, maize, and rice. Nowadays, healthy and nutritious product requirement has been increasing. Thus, research on the nutrition-rich but neglected crop is becoming visible nowadays to ensure global food security and to satisfy the nutritional need. Research indicated that moringa tree leaf powder has good nutritional value, but it is not yet customized and properly consumed. Method. The study is aimed at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…The percentage of crude fiber increased along with the increase in the concentration of added Moringa leaves flour. This study is also supported by Zula et al, (2021), which state that the addition of Moringa leaves flour will increase the crude fiber content of the product. High fiber content in a product is expected to be in pasta or other cereal products.…”
Section: Crude Fiber Contentsupporting
confidence: 75%
See 1 more Smart Citation
“…The percentage of crude fiber increased along with the increase in the concentration of added Moringa leaves flour. This study is also supported by Zula et al, (2021), which state that the addition of Moringa leaves flour will increase the crude fiber content of the product. High fiber content in a product is expected to be in pasta or other cereal products.…”
Section: Crude Fiber Contentsupporting
confidence: 75%
“…The research conducted by Prayitno & Rahim (2021) stated that adding Moringa oleifera leaves flour by 15% increased the protein content of chicken nuggets. A study reported that fortification of Moringa oleifera leaves flour will improve the protein content in noodle products (Zula et al, 2021).…”
Section: Protein Contentmentioning
confidence: 99%
“…A study conducted by Getachew & Admassu (2020) showed that pasta produced from moringa, oats, and wheat had approximately similar results compared to ours for fat, ash, and fibre contents except for the ratios of 25% moringa and 25% oats where fat and ash were higher. Regarding protein content, pasta produced from only moringa and wheat had nearly similar (9.7%–10.9%) content or a bit less since in the current study corn was included which increased the content (Zula et al ., 2021). Only one study was found to have one of the ingredients from current study as gluten free pasta.…”
Section: Resultsmentioning
confidence: 99%
“…(2015) found a range of standard fungal counts of 30–56 × 10 1 CFU g −1 in noodles. The total fungal count of noodles lies in the range of 5.9 to 2.6 CFU g −1 (Zula et al ., 2021). The total fungal count in cucumber pomace‐enriched noodles lies between 0.9 and 3.0 log CFU (Saad et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…total plate count of noodles was 6.7 to 3.65 CFU g −1 (Zula et al, 2021). The total bacterial count in cucumber pomace-enriched noodles lies between 1.9 and 6.4 log CFU (Saad et al, 2021).…”
Section: Total Plate Count Of Noodlesmentioning
confidence: 93%